THE EFFICACY OF DHANYA PANCHAK KWATHA IN ACUTE DIARRHEA IN CHILDREN - B.S. Sharma (International Journal of Ayurveda and Pharma Research, 2016)
Diarrhea is the major health problem in developing countries. It kills more than 1 million children annually. According to Ayurveda due to intake of Aama producing Nidana, Vata gets vitiated because of malfunctioning of Samana- apana vata leading to Jatharagni mandya and Shunyata of Koshtha (mal absorption in large intestine) causes the increase in Dravata of stool in Pakvashya and result in Atisara. so Aama and Vata are the major factor in etiopathogenesis of diarrhea. So Deepan and Pachan medicines are required to break the Samprapti of Atishara. in addition to above Grahi dravyas are also indicted to maintain the consistency of stool. As per above principle Dhanya panchak kwatha in group A and Balachaturabhadra in group B was selected to study. Balchaturbhadra churna has been indicated by Bhaishajyaratnavali in Balatisara Chikitsa. 60 children aged 2 to 10 years were selected in 2 groups. Group A children were treated with Dhanyapanchak kwatha and group B children were treated with Balachaturbhadra churna with lukewarm water for 7 days in dose of 300 mg per kg and 100 mg per kg respectively. Frequency of stools, thirst, skin pinch and consistency of stools were the main criteria to assess the result of medicines.Though the results were observed significant in both Groups in all parameters but the Dhanya Panchak Kwatha proved superior in reducing frequency of stool and improvement in stool consistency. Whereas Comparatively better results observed in thirst and skin turgor. Study proves the significance of Grahi dravya and Intake of lukewarm water in Atisara.